"A condom is compulsory": A qualitative study of condom use and negotiation strategies among female sex workers in Nepal. Issue 8 (13th September 2020) - Huber-Krum, Sarah; Karandikar, Sharvari; Gezinski, Lindsay
ABSTRACT: The objective of this qualitative study was to understand Nepali female sex workers' (FSWs) condom negotiation strategies. In 2016, we conducted 30 semi-structured, in-depth interviews with street- and brothel-based FSWs residing in Kathmandu, Nepal. Participants reported that their first entry into sex work typically occurred between the ages of 17–32, and the average duration of women's involvement with sex work was 8 years. FSWs reported high knowledge and awareness of condoms, and many women had used various sexual and reproductive health services. FSWs used three types of negotiation strategies: withholding or refusing sex, providing risk information, and direct request. While some FSWs believed that these strategies were useful and successful, we found that, for some women, condom negotiation strategies were difficult to implement due to fear of abuse and threats of violence by clients. Condom negotiation was further complicated by poverty and substance abuse, and several narratives revealed the influence of gender and social norms on safe sexual practices. The findings highlight the need for improved sexual health interventions that incorporate a range of negotiation strategies and techniques (e.g., nonverbal communication and reward strategies) and aim to mitigate harm and violence against FSWs.